Anatomical defences against bark beetles relate to degree of historical exposure between species and are allocated independently of chemical defences within trees. (25th November 2018) - Mason, Charles J.; Keefover‐Ring, Ken; Villari, Caterina; Klutsch, Jennifer G.; Cook, Stephen; Bonello, Pierluigi; Erbilgin, Nadir; Raffa, Kenneth F.; Townsend, Philip A.
Abstract: Conifers possess chemical and anatomical defences against tree‐killing bark beetles that feed in their phloem. Resins accumulating at attack sites can delay and entomb beetles while toxins reach lethal levels. Trees with high concentrations of metabolites active against bark beetle‐microbial complexes, and more extensive resin ducts, achieve greater survival. It is unknown if and how conifers integrate chemical and anatomical components of defence or how these capabilities vary with historical exposure. We compared linkages between phloem chemistry and tree ring anatomy of two mountain pine beetle hosts. Lodgepole pine, a mid‐elevation species, has had extensive, continual contact with this herbivore, whereas high‐elevation whitebark pines have historically had intermittent exposure that is increasing with warming climate. Lodgepole pine had more and larger resin ducts. In both species, anatomical defences were positively related to tree growth and nutrients. Within‐tree constitutive and induced concentrations of compounds bioactive against bark beetles and symbionts were largely unrelated to resin duct abundance and size. Fewer anatomical defences in the semi‐naïve compared with the continually exposed host concurs with directional differences in chemical defences. Partially uncoupling chemical and morphological antiherbivore traits may enable trees to confront beetles with more diverse defence permutations that interact to resist attack. Abstract : Plants defend against attacks by multiple mechanisms spanning chemical and physical components. We investigated how two pine species with varying historical exposure to the mountain pine beetle integrate anatomical and chemical defences. We found that the pine species that had more frequently encountered mountain pine beetle in recent history had superior anatomical defences than the species now becoming increasingly exposed due to climate change. In both pines, metrics of anatomical defences were largely unrelated to concentrations of important chemical traits, suggesting independent allocation that possibly presents beetles with more diverse permutations of defence.